Impact of urology simulation boot camp in improving endoscopic instrument knowledge. (11th July 2018) - Hanchanale, Vishwanath; Kailavasan, Mithun; Rajpal, Sanjay; Koenig, Philip; Yiasemidou, Marina; Palit, Victor; Rogawski, Karol; Eardley, Ian; Terry, Tim; Jain, Sunjay; Myatt, Andrew; Biyani, Chandra Shekhar
Abstract : Objective: Education and training of surgeons has traditionally focused on the development of individual knowledge, technical skills and decision making. Knowledge about endoscopic instruments is one of the core elements of urological training. We assessed the precourse knowledge of newly appointed urology trainees and the impact of boot camp in improving their knowledge. Methods: Newly appointed specialty trainees in urology took part in a pilot 5-day urology simulation boot camp (USBC). The aim of the USBC was to improve their confidence, procedural performance and non-technical skills, with one of the modules looking at the trainees' knowledge about common endoscopic instruments in urology. Delegates were first asked to identify and assemble the instruments, followed by one-to-one teaching about the instruments. An Objective Structured Assessment Tool was used to assess their knowledge in the identification and assembly of the cystoscope, resectoscope and optical urethrotome, before and at the end of the course. Results: Data of two successive boot camps were collected to assess knowledge of instruments of newly appointed urology trainees. Majority of the trainees had good precourse knowledge of the cystoscopy kit, with 84% able to correctly identify the parts. Seventy-six per cent of candidates were able to identify the resectoscope equipment, but only approximately a third of trainees were able to correctly identify the urethrotome kit. The assembly of cystoscope, resectoscope and urethrotome was performed correctly in 74%, 42% and 32% at baseline and 94%, 90% and 77% postcourse, respectively. Overall performance improved significantly in the postcourse assessment (<0.001). Conclusion: This urology boot camp has addressed gaps in trainees' core equipment knowledge and guided them to improve their knowledge with respect to identification and assembly of cystoscope, resectoscope and urethrotome.